Effect of Centella asiatica leaf extract on the transgenic Drosophila model of Parkinson’s disease (Cuestiones de Fisioterapia, 2025)
Parkinson's disease (PD) is a progressive neurodegenerative disease that causes motor and cognitive deficits due to α-synuclein aggregation and dopaminergic neuron loss. One of the most important factors in PD pathogenesis is oxidative stress. Parkinson disease transgenic Drosohphila model is used to examine the neuroprotective potential of Centella asiatica, a medicinal plant with antioxidant qualities. TH-GAL4 females were crossed with UAS-SNCA males to create transgenic PD model flies that express human α-synuclein in dopaminergic neurons.